Question Sequences and Salience in TED Talks - Michele Cardo; Agnès Celle (Anglophonia)
Salience is often used in linguistics to refer to the importance given to a certain part of a discourse such as a word, phrase, or grammatical function (Col, 2011). As such, question sequences can be considered a tool used to make a certain topic more salient because they represent the repetition of a certain linguistic device. Moreover, the repetitive nature of a question sequence has the tendency to affect the audience’s attention in a particular way and might lead to the perception of greater emphasis on topics addressed in the question sequences. It may be difficult to quantify emphatic salience because of the subjective nature of discourse perception. However, there are some measures which can be used and have been discussed in previous literature. Following Falk (2014:4)’s idea that “the key characteristic of salience is its function to encode predictability or likelihood of continuous or discontinuous (previous / next) mention of a discourse part in the mental model throughout time,” this paper considers how question sequences are used by TED talk presenters to create a discourse framework which prompts the audience to understand the importance of a certain subject. Furthermore, question sequences in TED talks may be used to manipulate the audience’s attention in either a forward- or backward-looking manner.Through the analysis of a transcribed corpus of TED talks in English, as studied in Celle and Liégeois (2021), this paper examines question sequences in a corpus of 18 transcribed TED talks by presenters with various backgrounds. Through a proposed hierarchy of question sequences, we attempt to understand how question sequences can be used to make a topic more salient and create a sense of anticipation on the part of the audience. This relates directly to previous work on linguistic salience and helps us to develop an understanding of how questions might play a role in presentational dialogue games.